MIGA Annual Report 2020 - Multilateral Investment Guarantee Agency (Washington, DC: Multilateral Investment Guarantee Agency, 2020)
MIGA’s mandate is to promote cross-border private investment in developing countries by providing guarantees (political risk insurance and credit enhancement) to investors and lenders. In FY20, MIGA issued nearly US$4 billion in new guarantees, helping mobilize over US$7 billion in total financing. FY20 projects will provide access to power to some 12.4 million people, procure US$4.3 million in goods locally each year, and avoid approximately 3 million tons of carbon dioxide equivalent (tCO2e) emissions per year. Of the 47 projects supported during FY20, 70 percent addressed at least one of the three strategic priority areas: IDA-eligible countries, fragile and conflict-affected situations (FCS), and climate change. Since its creation, MIGA has issued over $59 billion in guarantees across 118 developing countries.